The effects of electromyostimulation training and basketball practice on muscle strength and jumping ability - Maffiuletti, N. A.; Cometti, G.; Amiridis, I. G.; Martin, A.; Pousson, M.; Chatard, J. C. (International Journal of Sports Medicine, 2000)
The aim of this study was to investigate the influence of a 4-week electromyostimulation training program on the strength of the knee extensors and the vertical jump performance of 10 basketball players. Electromyostimulation sessions were carried out 3 times weekly; each session consisted of 48 contractions. Testing was carried out before and after the electromyostimulation training program (week 4) and once more after 4 weeks of normal basketball training (week 8). At week 4, isokinetic strength increased significantly (p < 0.05) at eccentric and high concentric velocities (between 180 and 360 x s(-1)); this was not the case for low concentric velocities (60 and 120 degrees x s(-1)). Electromyostimulation training increased also isometric strength at the two angles adjacent to the training angle (p < 0.01). Squat jump increased significantly by 14% at week 4 (p < 0.01), whereas counter movementjump showed no change. At week 8, gains in isokinetic, isometric strength and squatjump performance were maintained and the counter movement jump performance increased significantly by 17% (p<0.01). Electromyostimulation as part of a short strength-training program enhanced knee extensor strength and squat jump performance of basketball players.